2019
DOI: 10.7710/2162-3309.2309
|View full text |Cite
|
Sign up to set email alerts
|

From Meow to ROAR: Expanding Open Access Repository Services at the University of Houston Libraries

Abstract: INTRODUCTIONThe rapidly changing scholarly communication ecosystem is placing a growing premium on research data and scholarship that is openly available. It also places a growing pressure on universities and research organizations to expand their publishing infrastructures and related services. DESCRIPTION OF PROGRAM To embrace the change and meet local demands, University of Houston (UH) Libraries formed a cross-departmental open access implementation team in 2017 to expand our open access repository service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Metadata, especially legacy metadata from a previous system, was routinely described as an obstacle to the use of a digital collection when the metadata is messy and nonstandard (Darcovich et al, 2018; Georgieva & Flinchbaugh, 2021; Gries et al, 2018; Kertesz et al, 2020; Rousidis et al, 2014; Waldron, 2017), inflexible (Allen et al, 2017; Fabian, 2006; Fallaw et al, 2021; Lutz and Meadow, 2006; Mannien, 2018; Shepard, 2013), idiosyncratic (Murphy, 2003; Wilkinson et al, 2017), inappropriate for the subject (Greenberg et al, 2009; Rousidis et al, 2014), or incompatible with the hardware and software environment (Darcovich et al, 2018; Klump et al, 2015). Metadata improvements were needed to improve user search experience (Darcovich et al, 2018; Dressler, 2016; Herrera, 2007; Jiang et al, 2015; Lee et al, 2018; Murphy, 2003; Owen & Michalak, 2015; Stolte et al, 2003); support multiple search functionalities (Jiang et al, 2015; Stolte et al, 2003); incorporate metadata from legacy material (Bond, 2006; Waldron, 2017; Zohner et al, 2019); add additional information to make the metadata rich and consistent (Georgieva & Flinchbaugh, 2021; Greenberg et al, 2009; Manninen, 2018; Philipson, 2020; Rousidis et al, 2014; Waldron, 2017; Wilkinson et al, 2017); and to improve interoperability between systems (Philipson, 2020; Powell & Moseley, 2021; Wu et al, 2016, 2019). Interoperability was a particular concern for those working with domain‐specific databases, where there is a need to share or aggregate data with other related systems (Gries et al, 2018; Stigler & Steiner, 2018; Stolte et al, 2003; Wilkinson et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Metadata, especially legacy metadata from a previous system, was routinely described as an obstacle to the use of a digital collection when the metadata is messy and nonstandard (Darcovich et al, 2018; Georgieva & Flinchbaugh, 2021; Gries et al, 2018; Kertesz et al, 2020; Rousidis et al, 2014; Waldron, 2017), inflexible (Allen et al, 2017; Fabian, 2006; Fallaw et al, 2021; Lutz and Meadow, 2006; Mannien, 2018; Shepard, 2013), idiosyncratic (Murphy, 2003; Wilkinson et al, 2017), inappropriate for the subject (Greenberg et al, 2009; Rousidis et al, 2014), or incompatible with the hardware and software environment (Darcovich et al, 2018; Klump et al, 2015). Metadata improvements were needed to improve user search experience (Darcovich et al, 2018; Dressler, 2016; Herrera, 2007; Jiang et al, 2015; Lee et al, 2018; Murphy, 2003; Owen & Michalak, 2015; Stolte et al, 2003); support multiple search functionalities (Jiang et al, 2015; Stolte et al, 2003); incorporate metadata from legacy material (Bond, 2006; Waldron, 2017; Zohner et al, 2019); add additional information to make the metadata rich and consistent (Georgieva & Flinchbaugh, 2021; Greenberg et al, 2009; Manninen, 2018; Philipson, 2020; Rousidis et al, 2014; Waldron, 2017; Wilkinson et al, 2017); and to improve interoperability between systems (Philipson, 2020; Powell & Moseley, 2021; Wu et al, 2016, 2019). Interoperability was a particular concern for those working with domain‐specific databases, where there is a need to share or aggregate data with other related systems (Gries et al, 2018; Stigler & Steiner, 2018; Stolte et al, 2003; Wilkinson et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…We additionally categorized papers according to their focus, and found that while many papers discuss sustainability broadly, few specifically discuss database migration: 17 papers in the corpus were primarily about migration, either in the form of case studies of a particular database migration or research about migration (Allen, 2017; Bruns et al, 2014; Choi, 2020; Davis, 2015; Doty et al, 2015; Dunn et al, 2016; Fabian, 2006; Fallaw et al, 2021; Klump et al, 2015; Matusiak et al, 2017; Murphy, 2003; Pierce, 2019; Shepard, 2013; Thakar & Szalay, 2010; Thomer et al, 2017, 2018; Trippel & Zinn, 2021). Six focused on database maintenance in preparation for migration (Darcovich et al, 2018; Dressler, 2014; Georgieva and Flinchbaugh, 2021; Walsh, 2010; Wu et al, 2016; Wu et al, 2019). 39 papers were about maintenance or sustainability of a system separate from migration (Bond, 2006; Dal Pra et al, 2019; Downs & Chen, 2010; Gordon et al, 2015; Greenberg et al, 2009; Greig & Nixon, 2007; Gries et al, 2018; Han, 2011; Herrera, 2007; Imker, 2020; Jeng et al, 2017; Jiang et al, 2015; Jones et al, 2000; Kertesz et al, 2020; Lafferty‐Hess et al, 2020; Le et al, 2015; Lee et al, 2018; Lutz & Meadow, 2006; Madsen & Oleen, 2013; Manninen, 2018; Marcial & Hemminger, 2010; Nagendra et al, 2001; Nie et al, 2021; Owen & Michalak, 2015; Park et al, 2018; Philipson, 2020; Post et al, 2019; Powell & Moseley, 2021; Reil...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A general description of diffraction is shown by the von Laue equations, which consider the beams as fields 22 . In this way, the diffraction patterns can be visualized in reciprocal space (Fig.…”
Section: Reciprocal Space Theory and Laue Diffractionmentioning
confidence: 99%